MANAGEMENT ANALYSIS OF MSME BUSINESS STRATEGIES IN ENCOURAGING THE ACCELERATION OF NATIONAL ECONOMIC RECOVERY IN GORONTALO PROVINCE - Antu, Yahya; Bakari, Luthfia; Laleno, Maryam (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to formulate an MSME business strategy management model in encouraging the acceleration of national economic recovery with a research focus, namely the identification of internal and external factors of MSMEs and the preparation of MSME strategy models. The population is determined by purposive sampling and purposive sampling. The data analysis used is a qualitative descriptive method, namely identifying various problems faced by MSMEs in Gorontalo province and analyzing them using SWOT analysis and then formulating a strategy model to overcome them. MSMEs are a very important sector and play an active role in the Indonesian economy. The role of MSMEs also includes the acceleration of Indonesia's economic growth. This is because there is a match between the role of MSMEs in providing jobs and the formation of added value. Especially the strategic management aspects that must be carried out by MSMEs both in increasing production, increasing the capacity of MSME human resources, capital, and marketing activities. Another thing is the importance of the government's role and attention to continue to encourage MSME players to increase their production and help market MSME products not only at the local level but can reach abroad. This activity is expected to immediately restore economic conditions in the current post-pandemic period for the better.